Prognostic Utility of the MEST-C Score Combined With Clinical Parameters in Hispanic Patients With IgA Nephropathy - Lyzinhawer Alza-Arcila; Esteban Echeverri-Fernández; Mauricio Restrepo-Escobar; Ligia Lorena Calderón; José Manuel Ustáriz; Luis Fernando Arias-Restrepo; Joaquín Roberto Rodelo-Ceballos (International Journal of Nephrology)
Conclusion: Performing the MEST score, especially the presence of sclerosing (S) and tubular fibrosis/atrophy (T) lesions combined with clinical variables are prognostic variables in the Hispanic population.